Effect of Dexamethasone on The Duration of Analgesia for Supraclavicular Brachial Plexus Block (KYAMC Journal, 2021)
Background: Brachial plexus block with Bupivacaine provides effective intraoperative anesthesia and analgesia. The use of dexamethasone along with local anesthetic has been shown to improve the duration of analgesia.Objective: To observe the effect of Dexamethasone on the duration of analgesia for Supraclavicular Brachial plexus block.Materials and Methods: A prospective, double-blind study was undertaken in patients scheduled for upper limb surgeries under supraclavicular brachial plexus block. patients were randomly divided into two groups, Group (BD) and B. Group B received 28 ml of 0.25% bupivacaine with 2 ml normal saline while Group BD received 28 ml of 0.25% bupivacain with 2ml (8mg) dexamethasone for supraclavicular brachial plexus block. The groups were compared regarding quality of sensory and motor blockade. All the information was recorded in data collection sheet. Data was processed and analysed with the help of computer program SPSS and Microsoft excel.Results: There was no significant difference between groups in respect of demographic and American Society of Anaesthesiologist (ASA) status. Mean age was found to 34.7±8.53 years. In Group (BD) , 63.3% were ASA I and 36.6% were ASA II. In Group B, 60% were ASA I and 40% were ASA II. It has become evident that satisfactory anaesthesia can be made possible by addition of adjuvant to local anaesthetic in brachial plexus block (in Group-BD). onset of sensory block was faster in Group BD (8.17 ± 1.4 min) than Group B (9.12 ± 1.68 min). Similarly mean onset time of motor block in group A was 12.26 ± 3.96 min, and 11.58 ± 3.68 min in group B. Our study shows that duration of motor block was 408.68±26.96 min and 380.26 ± 24.11 min in group BD and Group B respectively.Conclusion: There was significantly prolonged duration of analgesia in addition of Dexamethasone without any unwanted effects.KYAMC Journal Vol. 11, No.-4, January 2021, Page 199-203